Linear Prediction of Sum of Two Poisson Process - Raheem, S. H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Our goal from this work is to find the linear prediction of the sum of two Poisson process ) ( ) ( ) ( t Y t X t Z + = at the future time 0 ), ( â‰¥ + Ï„ Ï„ t Z and that is when we know the values of ) (t Z in the past time and the correlation function ) (Ï„ Î²z